On “epistemic injustice” and victimization in prisons - Jörg Alfred Stippel; Paula Pérez; Marcelo Barrìa (Revista Brasileira de Direito Processual Penal, 2023)
The article looks for reasons that explain the different results of criminal investigations conducted inside and outside prisons. We ask if and how the concept of epistemic injustice, as developed by Miranda Fricker, helps to understand those variations. The underlying hypothesis is that epistemic injustice is a symptom of a wider problem. The authors assume that the treatment of victims of violent crime inside prison has structural rather than interpersonal explanations. In a qualitative approach the study uses data from a series of semi-structured interviews with prisoners and prison officers (40 interviews in total). It explores the dynamics of the decision to report crime committed inside prisons and the role of different institutions involved in the investigation of these crimes from the perspective and experience of prisoners and prison officers. As result it is argued, that Fricker’s concept of epistemic injustice is not very helpful when it comes to understand epistemic injustice suffered by victims of violent crime inside prison. It can be better understood in the terms of epistemic oppression used by Dotson. Thus, it is not about assigning blame but how to change the underlying social relations and institutions that subordinate prisoners on epistemic grounds.